2006
DOI: 10.1105/tpc.106.045633
|View full text |Cite
|
Sign up to set email alerts
|

NPS6, Encoding a Nonribosomal Peptide Synthetase Involved in Siderophore-Mediated Iron Metabolism, Is a Conserved Virulence Determinant of Plant Pathogenic Ascomycetes

Abstract: NPS6, encoding a nonribosomal peptide synthetase, is a virulence determinant in the maize (Zea mays) pathogen Cochliobolus heterostrophus and is involved in tolerance to H2O2. Deletion of NPS6 orthologs in the rice (Oryza sativa) pathogen, Cochliobolus miyabeanus, the wheat (Triticum aestivum) pathogen, Fusarium graminearum, and the Arabidopsis thaliana pathogen, Alternaria brassicicola, resulted in reduced virulence and hypersensitivity to H2O2. Introduction of the NPS6 ortholog from the saprobe Neurospora cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
345
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(369 citation statements)
references
References 69 publications
(82 reference statements)
14
345
2
1
Order By: Relevance
“…The discovery of antibiotics in Penicillium crysogenum is well known, and fungi-particularly those occupying unique ecological niches-continue to be a source for their discovery (31,32). Iron-binding siderophores, synthesized via nonribosomal peptide synthase-mediated pathways, are involved in iron scavenging, uptake, and sequestration, and have been shown to act as virulence factors in various pathogenic fungi (33). Some secondary metabolites act as "toxins," affecting/disrupting host tissues and processes; for example, the Cochliobolus carbonum HC toxin targets host histone deacetylases and is required for infection of maize cultivars that harbor the Hm resistance gene, but not of cultivars that lack Hm (34).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of antibiotics in Penicillium crysogenum is well known, and fungi-particularly those occupying unique ecological niches-continue to be a source for their discovery (31,32). Iron-binding siderophores, synthesized via nonribosomal peptide synthase-mediated pathways, are involved in iron scavenging, uptake, and sequestration, and have been shown to act as virulence factors in various pathogenic fungi (33). Some secondary metabolites act as "toxins," affecting/disrupting host tissues and processes; for example, the Cochliobolus carbonum HC toxin targets host histone deacetylases and is required for infection of maize cultivars that harbor the Hm resistance gene, but not of cultivars that lack Hm (34).…”
Section: Discussionmentioning
confidence: 99%
“…Iron-chelating siderophores are also utilized by pathogens during infection (Haas et al, 2008). NPS6, encoding a non-ribosomal peptide synthetase involved in siderophore biosynthesis, is a functionally conserved virulence factor of different necrotrophic ascomycetes including A. brassicicola (Oide et al, 2006). Arabidopsis rbohDrbohF double mutants, disrupted in NADPH oxidase function, exhibit increased susceptibility to wildtype A. brassicicola infection but unaltered responses to a strain harboring a loss of function NPS6 allele (Oide et al, 2006).…”
mentioning
confidence: 99%
“…Phytopathogenic bacteria and fungi can use siderophores to multiply in the host and to promote infection (Expert, 1999;Haas et al, 2008). Oide et al (2006) demonstrated that in four ascomycete species, Cochliobolus miyabeanus, Cochliobolus heterostrophus, Fusarium graminareum, and Alternaria brassicicola, siderophores are required for resistance to hydrogen peroxide and for full pathogenicity on their respective hosts maize (Zea mays), rice (Oryza sativa), wheat (Triticum aestivum), and Arabidopsis. Likewise, the fire blight-causing agent Erwinia amylovora takes advantage of its siderophore deferrioxamine (DFO) for the infection of apple (Malus domestica) seedlings and flowers and for the resistance to hydrogen peroxide (Dellagi et al, 1998).…”
mentioning
confidence: 99%